Study of the antibacterial activity of ginger extract in comparison with the antibiotics gentamicin, azithromycin and doxycycline on Escherichia coli isolated from broilers in Tartous - afef, alaa (Latakia University Journal -Biological Sciences Series, 2025)
Escherichia coli causes significant economic losses in broiler farms due to high mortality rates, low feed conversion efficiency, and delayed growth. This risk increases with the random use of antibiotics in its treatment, in addition to the emergence of resistance to these antibiotics, which may reach humans. Accordingly, this research was conducted with the aim of isolating and confirming Escherichia coli infection in some broiler farms in Tartous Governorate and studying the effectiveness of some antibiotics used in its treatment and comparing them with ginger extracts, thus finding natural alternatives to commercial antibiotics and reducing their effects. Samples were collected during the period from 13/11/2022 to 22/11/2023 from different areas: (Amrit, Beit Al-Khatib, Jaditi, Matrouh, Qamsiyeh, Khirbet Al-Maazah, Marqia, Zahwiya, Safliyeh, Al-Hamidiyah, Saya). Symptoms were recorded, pathological dissection was performed, samples were cultured in nutrient broth and incubated at (37) C, then cultured on specific media to diagnose the presence of Escherichia coli bacteria. Sensitivity tests were conducted for three antibiotics, namely azithromycin, gentamicin and doxycycline, and compared with alcoholic and aqueous ginger extracts. The results indicate that the alcoholic ginger extract is superior to the rest of the studied antibiotics with high statistical significance and an average inhibition diameter of (11.84), followed by aqueous ginger with an average inhibition diameter of (10.47), azithromycin with an average inhibition diameter of (10.47), followed by gentamicin with an average inhibition diameter of (10.42), then the antibiotic doxycycline with an average inhibition diameter of (9.80). Thus, the extract shows encouraging efficacy that may qualify it as a natural alternative to antibiotics. Keywords: Escherichia coli, chicken, antibiotic sensitivity, ginger.